DESKRIPSI PERILAKU KONSUMEN DALAM KEPUTUSAN PEMBELIAN TERHADAP OBAT HERBAL (HERBAL MEDICINE) - Shalahuddin, Laode; Wijayanti, Risna (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The health industry is included in an industry that experienced an increase in 2019-2020 due to the Covid-19 (Corona Virus Disease) pandemic. This can provide benefits for Indonesia because it is one of the largest biopharmaceutical (medicinal) producing countries in the world. The objective of this research is to describe the behavior of consumers in their decision to purchase herbal medicine in the largest biopharmaceutical plant-producing region in Indonesia. The data of this research was harvested by distributing questionnaires to a sample of 120 respondents living in the said region. Using frequency distribution and description, this study finds that there are three factors shaping consumer behavior, they are psychological factor, i.e. learning, perception, motivation, and attitude and belief, social factor, i.e. culture, family, group references and social class, and marketing factor, i.e. product, price, place, and promotion. The benefit of this research is to assist herbal medicine business actors in the health industry in recognizing people's consumption behavior towards herbal medicines and is useful for future researchers in enriching discussions that focus on herbal medicine (herbal medicine).